Rasionalitas Mitigasi Covid-19 Masyarakat Madura Melalui Kearifan Lokal Qashidah Burdah - Dayanti, Fitria; Az Zahra, Hanifah; Firdaus, Nadzir Ahmad (Prodi Sosiologi FISIP Universitas Teuku Umar, 2023)
Various efforts have been made by both the government and society to minimize and overcome the impacts caused by the spread of Covid-19. The Indonesian government is mitigating Covid-19 through PSBB, PPKM, vaccination policies and tightening the use of health protocols. The community makes mitigation efforts with a cultural approach based on local wisdom. The people of Madura Island carry out Qhasidah Burdah activities as an effort to mitigate Covid-19, one of the most intense of which is the people of Tambak Agung Hamlet, Labang District. The problem that emerged was that when the government banned all forms of activities involving gatherings, Madurese people actually held gatherings as an effort to mitigate Covid-19 through Qhasidah Burdah. The aim of this research is to analyze the rationality of the actions of the Madurese community in mitigating Covid-19 through Qashidah Burdah. The method used in this research is qualitative using Max Weber's Social Action Theory analysis knife. The research results show that Madurese people's actions in carrying out Qhasidah Burdah as Covid-19 mitigation are classified into four types, including instrumental rationality actions, value-oriented rationality actions, and traditional actions. Indonesian society is full of local wisdom, it is hoped that the government will always consider this aspect in every policy implemented in the future.